Application of medical information technology during the Antarctic research - Shustova, I. (Ukrainian Antarctic Journal, 2012)
This article has describe process of development and testing of the virtual network for telemedicine monitoring in Antarctica region for permanent health control. Results could be used for extremal telemedicine system applications.